Pengaruh Belanja Modal dan Pendapatan Asli Daerah Terhadap Belanja Pemeliharaan dalam Realisasi Anggaran Pemerintah Kota Kediri (studi pada pemerintah kota kediri Th 2012-2016) - Setya Ramadani (Universitas Nusantara PGRI Kediri, 2019)
The background of this research is that the implementation of regional autonomy is characterized by fiscal decentralization which indicates the delegation of authority from the central government to regional governments to regulate their own regions autonomously. With the enactment of regional autonomy, it is intended that autonomous regions have the right, authority, and obligation to self-regulate government affairs and the interests of the community. The Effect of Capital Expenditures and Regional Original Income (PAD) on Maintenance Expenditures in the Realization of the Kediri City Government Budget. (Study on the City Government of Kediri in 2012 – 2016). The aims of this study are (1) to determine whether or not capital expenditures have an effect on maintenance expenditures in the Kediri City Government. (2) To find out whether or not local revenue has an effect on maintenance spending in the Kediri City Government. (3) To determine the effect of capital expenditure and local revenue simultaneously on maintenance expenditure in the City Government of Kediri. The data used in this study is secondary data, in the form of the realization of the local government of Kediri in the period 2012-2016. The research approach uses a quantitative approach. The analysis technique used is multiple linear analysis, taking into account the classical assumptions, namely normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. The hypothesis testing used is simultaneous statistical test (F test) and partial statistical test (t test) and with a significance level of = 5%. Data analysis using SPSS for windows version 23 program. The results of this study partially found that capital expenditure had no significant effect on maintenance expenditure, PAD had a significant effect on maintenance expenditure. The results of the study simultaneously show that capital expenditure and PAD have a significant effect on maintenance expenditure